MARKETING DIGITAL: uma proposta de ferramenta de auxílio à gestão da Comunicação para micro e pequenas empresas de serviços - VERAS, Thaís Frota de Albuquerque (2023)
We propose a new framework to assist in communication management for micro and small companies in the service sector. It is a qualitative applied research whose objective was based on the use of Generative Artificial Intelligence and Natural Language Processing tools. Therefore, the main difficulties related to marketing reported by the target audience, which are micro and small entrepreneurs. Different strategies were used to collect data for the study: bibliographical research, pre-test, evaluation and documentary research, semi-structured interview, experimentation, initial design of the prompts and proof of concept. The study addressed concepts related to Organizational Communication and possible ways to approach the target audience in an environment dominated by digital platforms. The historical panorama and the main concepts related to marketing were also presented and the benefits, possibilities and limitations of the use of Generative Artificial Intelligence in organizational management were discussed.